2017
DOI: 10.1515/prilozi-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hypoglycemia: Risk Factors and Outcomes

Abstract: background and aims:Severe neonatal hypoglycemia (HG) leads to neurologic damage, mental retardation, epilepsy, personality disorders, impaired cardiac performance and muscle weakness. We aimed to assess the clinical characteristics of children with hypoglycemia in a random population of newborns. Patients, methods and results: We investigated 84 patients (M:F=35:48) born at the University Clinic for Gynecology and Obstetrics in Skopje (hospitalized in the NICU) who were found to have hypoglycemia. In total 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
(22 reference statements)
2
13
0
Order By: Relevance
“…In current study birth asphyxia was more common neonatal risk factor than early septicaemia and RDS which was similar to study done by Dhananjaya CP et al, Burden et al and Manjunatha BR et al 11,14,12 Early septicemia was more common in the study done by Indira P et al and Stomnaroska et al and RDS was more common in the study by Bhand SA et al so that these are not similar to current study. 13,17,16 Most common symptoms of hypoglycemia were poor feeding, lethargy, jitteriness, seizure and respiratory abnormality which was similar to study done by Dhananjaya 11,13,16,18,12,8,10,15 In the current study, blood glucose level below 30 mg/dl was more commonly seen in neonates having more than one episode of hypoglycemia. The blood glucose levels at admission were in lower range in neonates who later had repeat episode of hypoglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…In current study birth asphyxia was more common neonatal risk factor than early septicaemia and RDS which was similar to study done by Dhananjaya CP et al, Burden et al and Manjunatha BR et al 11,14,12 Early septicemia was more common in the study done by Indira P et al and Stomnaroska et al and RDS was more common in the study by Bhand SA et al so that these are not similar to current study. 13,17,16 Most common symptoms of hypoglycemia were poor feeding, lethargy, jitteriness, seizure and respiratory abnormality which was similar to study done by Dhananjaya 11,13,16,18,12,8,10,15 In the current study, blood glucose level below 30 mg/dl was more commonly seen in neonates having more than one episode of hypoglycemia. The blood glucose levels at admission were in lower range in neonates who later had repeat episode of hypoglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…In a study done by Stomnaroska, et al found neonatal hypoglycemia was a signi icant factor in the overall neonatal mortality and infections, But Spearman tests showed weak direct correlation, without statistical signi icance [19]. Similar indings was found on a Study done by Islam, et al [20], showing that mortality was higher among the septic newborn with hyperglycemia (50%) compared to normoglycaemic patient (10.8%) and the difference was statistically signi icant (p < 0.05) between two groups [20]. Yadav, et al found the incidence of culture positive sepsis was 6.5% of the total cases of suspected sepsis, which was much lower than the present study [21].…”
Section: Discussionsupporting
confidence: 66%
“…Severe and prolonged hypoglycemia can result in serious neurodevelopmental abnormalities and can cause death. Therefore, timely identi cation of risk factors and interventions prevent neonates from unwanted complications of hypoglycemia [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%